Forced convection in a branching channel with partly elastic walls and inner L-shaped conductive obstacle under the influence of magnetic field - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2019)
In this study, forced convection in a branching channel with partly elastic walls is examined under the effects of magnetic field. Also, a conductive L-shaped obstacle is used to control flow field. Galerkin weighted residual finite element method is used for the solution of the governing equations. The Arbitrary-Lagrangian-Eulerian method is utilized for the description of the fluid motion with the elastic walls in the bifurcating channel in the fluid-structure interaction model. Effects of various pertinent parameters such as Reynolds number (between 100 and 500), elastic modulus of flexible wall (between 10(6) and 10(9)), size of the elastic part (between 2H and 32H), Hartmann number (between 0 and 20), size of the obstacle (d(1) between 0.1H and 0.45H), inclination of the obstacle (between -90 and 90) on the fluid flow characteristics and convective heat transfer features are examined. It was observed that the size and elastic modulus of the flexible wall are effective on the redistribution of separated zones for the horizontal branching channel. The average Nusselt number reduces with the bigger size of the elastic wall and the amount of reduction is in the range of 8% and 9%. Magnetic field suppresses the separated flow regions and increases the average heat transfer rate. The average Nusselt number enhancements are 33.9% and 12.5% for lower and upper hot walls of the horizontal bifurcating channel when configurations in the absence and presence of magnetic field (at the highest strength) are compared. It was observed that the size and orientation of the L-shaped obstacle have significant effects on separated flow regions and heat transfer rate and therefore can be used as an excellent control tool. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: MHD flow; Branching channel; Finite element method; L-shaped obstacle; Elastic